A Rare Case of Metaplastic Breast Carcinoma with Squamous Differentiation in Young Female: A Case Report - Agustina, Rohana (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2022)
Background. Metaplastic breast carcinoma is a very rare breast cancer, only about 0.2